2021
DOI: 10.3389/fnins.2021.621501
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of the cGAS-STING Pathway in CNS Pathologies

Abstract: Neuroinflammation driven by type-I interferons in the CNS is well established to exacerbate the progression of many CNS pathologies both acute and chronic. The role of adaptor protein Stimulator of Interferon Genes (STING) is increasingly appreciated to instigate type-I IFN-mediated neuroinflammation. As an upstream regulator of type-I IFNs, STING modulation presents a novel therapeutic opportunity to mediate inflammation in the CNS. This review will detail the current knowledge of protective and detrimental S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 113 publications
0
26
0
Order By: Relevance
“…There is mounting evidence that IFN-I propagate inflammatory processes during normal aging ( 94 , 95 ). Baruch and colleagues demonstrated that inhibition of IFN-I signaling alleviated the cognitive decline observed in aged mice ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence that IFN-I propagate inflammatory processes during normal aging ( 94 , 95 ). Baruch and colleagues demonstrated that inhibition of IFN-I signaling alleviated the cognitive decline observed in aged mice ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence for an association of the pathways associated with type I IFNs with neuroinflammation and neurodegenerative diseases just recently reviewed by Fryer A et. al ( 36 ). Therefore, the cGAS-STING or RIG-MAVS pathways can also be involved in the initiation of an inflammatory response through the production of type I IFN in the absence of pathogens.…”
Section: Unfolded Protein and Integrated Stress Responses - Between C...mentioning
confidence: 99%
“…There are numerous preclinical studies of cGAS-STING activators designed to treat cancer, and some designed to treat autoimmune diseases [ 149 ]. Accumulating evidence has indicated the cGAS-STING pathway in driving neuroinflammation of neurodegenerative diseases, thus inhibition of this pathway represents a viable therapeutic in the treatment of neurodegenerative diseases.…”
Section: Cgas-sting Pathwaymentioning
confidence: 99%